Room‐temperature phosphorescence materials from crystalline to amorphous state. Issue 1 (15th July 2022) - Xu, Zixuan; He, Yixiao; Shi, Huifang; An, Zhongfu
Abstract: Room temperature phosphorescence (RTP) in metal‐free organic materials has attracted considerable attention due to its rich excited state properties, high quantum efficiency, long luminescence lifetimes, etc., showing great potential in organic optoelectronic devices, bioimaging, information anti‐counterfeiting, and so forth. The crystals have excellent rigidity and clear molecular packing patterns, which can effectively avoid non‐radiative transitions of excitons for phosphorescence enhancement. In the early stages, researchers paid great attention to the regulation of RTP performance in crystalline states. However, due to the complex preparation and poor processability of crystals, amorphous materials with RTP features have become a new research topic recently. This perspective aims to summarize the recent advances of RTP materials from crystalline to amorphous states, and analyze their molecular design strategies and luminescence mechanisms in detail. Finally, we prospect the future research directions of amorphous RTP materials. This perspective will provide a guideline for the future study of advanced RTP materials.